A clinical evaluation of tooth bleaching treatment using a dual-barrel in-office whitening system - Lan, Wen C.; Yusuf, Andi S. H; Syam, Syamsiah; Natsir, Nurhayaty; Qiu, Youjin; Ruslin, Muhammad; Saito, Takashi (Hasanuddin University, 2019)
Objective: This study aimed to evaluate the whitening effect and tooth sensitivity after bleaching treatments using iBrite in-office whitening system.Methods: The clinical report accommodated 27 patients using the iBrite in-office whitening system for bleaching treatments. Prior to the procedure, patients were screened for eligibility and underwent basic tooth cleaning. Recorded data of before and after treatments including clinical images, VAS scales, and VITA scales were assessed. Follow-ups were completed three months and six months after the in-office treatment.Results: After treated with iBrite in-office whitening systems, on average 6.3 shades of tooth color change were observed in 27 patients. In term of tooth sensitivity, male patients are more likely to feel sensitive after the treatments compared to the female patients. Most teeth sensitivity relieved in three to four days, and no other sensitivity was observed 6 months after the original in-office treatment.Conclusion: The iBrite in-office whitening system provides a fast, comfortable and convenient tool for tooth whitening. The low-irritating, yet still professional-grade whitening effect makes it as an ideal tooth whitening system to use in the dental office.